Rozwiązane

Rozwiąż równania
a.-3x =2x -10
b.2x -2 =7-x
c.10=4-2x
d.0,5y=7-3y
e.-2x +1=4
f.2*(3t+1)=x
g.2t -(3t +1)=6
h.-(4+x)=6*(1-x)
i.4*(x-1)=6*(1*x)



Odpowiedź :

Odpowiedź:

a.

-3x =2x -10

-3x - 2x = -10

-5x = -10    /:(-5)

x = 2

b.

2x -2 =7-x

2x + x = 7 + 2

3x = 9

x = 3

c.

10=4-2x

2x = 4 - 10       /:2

x = -6/2 = -3

d.

0,5y=7-3y

0,5y + 3y = 7

3,5y = 7     /:3,5

y = 2

e.

-2x +1=4

-2x = 4 - 1     /:(-2)

x = -3/2 = -1 1/2

f.

2*(3t+1)=x  

x = 6t + 2

g.

2t -(3t +1)=6

2t - 3t - 1 = 6

-t = 6 + 1        /*(-1)

t = -7

h.

-(4+x)=6*(1-x)

i.

4*(x-1)=6*(1*x)

4x - 4 = 6x

4x - 6x = 4

-2x = 4      /:(-2)

x = 2

Szczegółowe wyjaśnienie: